Action research and collaborative reflective practice in English language teaching. Issue 1 (2nd January 2022) - Godínez Martínez, Jovanna
ABSTRACT: The purpose of this investigation was to explore how reflective practice (RP) could be implemented and systematized in diverse ELT Mexican contexts in order to foster continuous professional development. Hence, this collaborative action research was conducted over aperiod of 22 months with different English Language Teaching (ELT) practitioners; 24 Mexican teacher educators and two in-serviceEnglish language teachers from Longford, Ireland and Texas, USA who were living and working in Mexico. The data was collected by means of classroom observations, feedback sessions, individual interviews, and professional dialogues–informal meetings, self-reporting, and text messaging. Overall, the findings of this investigation showed that teachers, who had the openness to challenge inconsistencies, gaps and at times fears in their teaching stances, beliefs and therefore practices, also had the willingness to carry out reflective actions that were guided by critical inquiry, collaboration with the researcher and modelled practices by other colleagues; enabling teacher effective engagement in reflective procedures as well as in personal continuous professional development processes.